DEVELOPMENT OF HUMAN RESOURCES FOR EDUCATORS AT NURUL IMAN INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL, PURWOREJO, PESAWARAN DISTRICT - Khoirunisa, Desti; Rahmadani, Rahmadani; Junaidah, Junaidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The problem in this study is the development and development of human resources for teaching staff at SMP IT Nurul Iman Purworejo, Pesawaran Regency; in terms of their professionalism as educators, it can be seen from the excellent performance and achievements of the teachers they have. The teacher's performance and achievements must be developed through various development strategies in the form of education and training as well as activities other than education and training that are followed. Therefore this research is to find out how to develop human resources for teaching staff at SMP IT Nurul Iman Purworejo, Pesawaran Regency. The method in this research is descriptive qualitative. Data sources were obtained from subjects (school principals, curricula deputy's heads, teachers and school partners) and objects (development of human resources for teaching staff at SMP IT Nurul Iman Purworejo, Pesawaran District). Data collection techniques used by researchers were observation, interviews and documentation. At the same time, the data analysis used is data reduction, data presentation (data display), and conclusion. The results of this study indicate that the development of human resources for teaching staff at SMP IT Nurul Iman Purworejo, Pesawaran Regency, has been reasonably good because a lot of coaching and development has been carried out to improve the performance and professionalism of teaching staff through strategies in the form of 1) Education and training, including In- house training, school partnerships, distance learning, tiered training and special training, short courses at universities or other educational institutions, internal coaching by schools, and further education. 2) Activities other than education and training include: Discussion of educational issues, seminars, workshops, research, writing books/teaching materials, making learning media, and making technology/artworks. These developments will likely improve the performance and professionalism of teachers in transferring knowledge to students so that national education can be realized.